2019
DOI: 10.28991/cej-2019-03091296
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Two Storey Car Showroom Using Pre-engineered Building (PEB) Concept Based on British Standards and Euro Code

Abstract: Majority of steel structures are used for low-rise single storey buildings mainly for industrial purpose. Steel structures are preferred for industrial buildings due to its higher strength to weight ratio as compare to RCC structures and steel structures also gives more free internal space by allowing long clear span between columns. Pre-engineered building (PEB) is a modern age concept of utilizing structural steel and optimizing the design by ensuring the economical integrity of the structure. The structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…A three main elements were needed for the modelling, concrete element, reinforcement bars element and the interface between the original column and the concrete jacket. The concrete was modelled using Solid 65 element, Figure 1 show the element discretion from ANSYS [23], the steel bars and horizontal stirrups were modelled using link 180 elements [20,23]. A column concrete geometry, steel bars, stirrups, and a jacket are all included in the model.…”
Section: Finite Element Materials Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…A three main elements were needed for the modelling, concrete element, reinforcement bars element and the interface between the original column and the concrete jacket. The concrete was modelled using Solid 65 element, Figure 1 show the element discretion from ANSYS [23], the steel bars and horizontal stirrups were modelled using link 180 elements [20,23]. A column concrete geometry, steel bars, stirrups, and a jacket are all included in the model.…”
Section: Finite Element Materials Modelsmentioning
confidence: 99%
“…The recommendation of Indian standard code IS 15988 (2013): Seismic Evaluation and Strengthening of Existing Reinforced Concrete Buildings -Guidelines issued by Bureau of Indian Standards [1,20] Using a factor of safety as 1.5, the failure load will be:…”
Section: Determination Of Load-carrying Capacitymentioning
confidence: 99%
“…The UHPC mix developed in this study used a combination of fine sand (FA), ultra-fine recovery material (UFR), cement, and different supplementary cementitious materials (SCMs), including slag cement (S) and silica fume (SF). Previous studies also reported using fine quartz particles in the UHPC matrix [19,22,23,30], but quartz is not locally available in Florida, with the majority of produced sand in this state coming from limestone aggregate. Silica powder was not used due to its relatively high costs.…”
Section: Materials Typesmentioning
confidence: 99%
“…Another research is to discuss a comparative study on a twostory car showroom using the pre-engineered building (PEB) concept based on British Standards and the Euro Code. The analysis compares structural behavior in terms of earthquake resistance, structure weight, and building stress ratio [9].…”
Section: Introductionmentioning
confidence: 99%